SISTEM INFORMASI AKUNTANSI ALOKASI DANA DESA DI DESA TANJUNG DALAM KECAMATAN PONDOK KUBANG KABUPATEN BENGKULU TENGAH - Shelvia Rezeki; Iwin Arnova (Jurnal Ilmu Akuntansi, 2019)
The purpose of this study is to determine whether the village apparatus of Tanjung Dalam has the ability to make financial reports of the Village Fund Allocation in accordance with the Accounting Information System and To determine whether village officials are weak in terms of financial administration in Accounting Information Systems Village Fund Allocation in Tanjung Dalam Village, Pondok Kubang Sub-district of Central Bengkulu Regency. This descriptive-based research is trying to describe the real picture of the phenomenon that occurs in the application of Accounting Information Systems on Village Fund Allocation in Tanjung Dalam Village, Pondok Kubang Sub-district of Central Bengkulu Regency. While the technique used in the form of direct observation to the village of Tanjung Dalam, Pondok Kubang Sub-district of Central Bengkulu Regency, who then conducted interviews and documentation studies.After the data collected and data analysis it can be drawn conclusion, namely: In the management of village funds in the village of Tanjung Dalam is in accordance with the accounting information system and already using computerized system. While the executor of Accounting Information System is the treasurer of the village itself that has been able to arrange the village finances properly in accordance with Accounting Information Systems. Any acceptance or expenditure of village funds is recorded in the village general treasury. It's just that there is still lack of supporting facilities for the officers who manage the village fund's financial report.